A Method of Locomotive Automatic Wheel Diameter Correction Based on GPS Speed - Fan JIANG; Yu WANG; Peng LI; Lihui HUANG; Weibo JIANG (机车电传动)
A method of automatic correction of wheel diameter using GPS speed was proposed, and the judgment conditions for entering the correction of wheel diameter and the compensation method of speed sequence were designed. The problem of extracting effective speed signals from GPS signals containing a lot of noise and time delay was solved, and the high precision (error is less than 2 mm) adaptive correction of locomotive wheel diameter was realized. The validity and accuracy of this method have been verified in the South African electric locomotive project.